"Dictionary contains the most accurate computer terminology "Online - Nada Muteb Saad Alotaib, Bushra Eidah Alsufyani (Journal of engineering sciences and information technology, 2018)
The translation is a requirement of all individuals, and through our study in the bachelor's IT department stage information (college of computers and information technology in Taif University), there were many students who suffer in their studies Computer English- language translation of computer terminology through (google search engines) is correctly and is compatible with the translation used in computer books. Hence the idea of the project was launched Dictionary of Computer Terms, based on research and not based on the order of the alphabet, which includes computer terms translated into Arabic to make it easier to understand the terminology during the study. And can add some of the characteristics of this dictionary to make it a competitor to other dictionaries.